Positive solutions for fractional differential equation at resonance under integral boundary conditions - Wang Youyu; Huang Yue; Li Xianfei (Demonstratio Mathematica, 2022)
By using the theory of fixed point index and spectral theory of linear operators, we study the existence of positive solutions for Riemann-Liouville fractional differential equations at resonance. Our approach will provide some new ideas for the study of this kind of problem.